1991
DOI: 10.1111/j.1365-2222.1991.tb00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between IgG1 and IgG4 antibodies to foods and the development of IgE antibodies to inhalant allergens. II. Increased levels of IgG antibodies to foods in children who subsequently develop IgE antibodies to inhalant allergens

Abstract: In the present investigation we have tested the hypothesis that children with a high IgG antibody response to foods have an increased risk of developing IgE antibodies to inhalant allergens. Sera from 106 children with an increased risk of developing IgE-mediated allergy were analysed. During the follow-up, in 54 of these children IgE antibodies to inhalant allergens appeared. A positive/negative IgG1 and IgG4 anti-food score was determined as described previously: sera from age-clustered unselected children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 30 publications
(32 reference statements)
2
26
0
1
Order By: Relevance
“…Children who were sensitized 21 or asthmatic 22 at 5 years had higher hen's egg‐specific IgG1 in early life. In addition, high‐risk infants with high food‐specific IgG1 were more likely to develop inhalant‐specific IgE, compared with subjects with low food‐specific IgG1 21, 23, 24. These findings suggest that raised food‐specific IgG1 could represent a predictive biomarker for future allergic disease, in high‐risk infants.…”
Section: Discussionmentioning
confidence: 82%
“…Children who were sensitized 21 or asthmatic 22 at 5 years had higher hen's egg‐specific IgG1 in early life. In addition, high‐risk infants with high food‐specific IgG1 were more likely to develop inhalant‐specific IgE, compared with subjects with low food‐specific IgG1 21, 23, 24. These findings suggest that raised food‐specific IgG1 could represent a predictive biomarker for future allergic disease, in high‐risk infants.…”
Section: Discussionmentioning
confidence: 82%
“…Accordingly, it has been previously proposed that high levels of IgG to some allergens early in life might predict the development of IgE sensitization later in life. 20,21,38 Therefore this area of investigation is very complex, and further studies are now needed to define how default and preatopic IgG responses can be better discriminated.…”
Section: Biological Implicationsmentioning
confidence: 98%
“…A group of sera were col lected from children under the age of 7 years with suspected atopy. These children participated in the study performed by Calkhoven et al [3], The sera were obtained after informed consent of the parents. For most subjects, no information was available on the dietary history' with respect to banana.…”
Section: Methodsmentioning
confidence: 99%
“…During an investigation of the antibody response to a broad panel of ingested foods [2,3], we found that the IgG antibody response to banana extract was much stronger than expected on the basis of quantities commonly in gested. This was particularly the case for lgG4 antibodies and much less so for IgGl or IgA antibodies.…”
Section: Introductionmentioning
confidence: 99%